2018
DOI: 10.1111/1751-7915.13261
|View full text |Cite
|
Sign up to set email alerts
|

Yeast culture dietary supplementation modulates gut microbiota, growth and biochemical parameters of grass carp

Abstract: SummaryGut microbiota contributes positively to the physiology of their host. Some feed additives have been suggested to improve livestock health and stimulate growth performance by modulating gut bacteria species. Here, we fed grass carp with 0 (control), 8% (Treat1), 10% (Treat2), 12% (Treat3) and 16% (Treat4) of yeast culture (YC) for 10 weeks. The gut microbiota was analysed by 16S rRNA gene V3‐4 region via an Illumina MiSeq platform. PCoA test showed that gut bacterial communities in the control and Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 62 publications
(98 reference statements)
3
18
1
Order By: Relevance
“…In the field of animal nutrition, the development of new potential prebiotics in animal husbandry industries is of current interest. Recently, high-throughput sequencing of 16S rRNA gene amplicons has been used to investigate potential beneficial effects of various feed additives (e.g., xylo-oligosaccharides and yeast cultures) on the gut microbial communities of farmed animals (Liu et al 2018; Pourabedin et al 2015). However, relatively few studies focused on the effects of liquor lees on the composition and function of livestock gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the field of animal nutrition, the development of new potential prebiotics in animal husbandry industries is of current interest. Recently, high-throughput sequencing of 16S rRNA gene amplicons has been used to investigate potential beneficial effects of various feed additives (e.g., xylo-oligosaccharides and yeast cultures) on the gut microbial communities of farmed animals (Liu et al 2018; Pourabedin et al 2015). However, relatively few studies focused on the effects of liquor lees on the composition and function of livestock gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the probiotics Lactobacillus ( Lactobacillus reuteri avibro ) and Bacillus ( Bacillus subtilis and Bacillus licheniformis ) exhibited the ability to increase nutrient digestibility and animal performance, and they reduced the abundance of pathogens ( Salmonella and Escherichia coli ) (Ahmed et al 2014). In pigs, some prebiotic products, such as xylo-oligosaccharides (XOS), β-mannanase, mannan-oligosaccharides, and yeast cultures have been used to modify gut microbiota composition, improve host immune response, stimulate the growth of more beneficial bacteria, and inhibit the colonization or abundance of pathogens by producing antimicrobial substances in humans and livestock (Barros et al 2015; De Maesschalck et al 2015; Liu et al 2018; Rastall and Gibson 2015). For instance, in broiler chicken, XOS feed additives modulate the gut microbiota and increase the abundance of the potential beneficial bacteria Lactobacillus and Bifidobacterium (Pourabedin et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For aquatic animals, numerous diseases are linked with the dysbiosis of host intestine microbiota ( Li et al, 2017 ; Dai et al, 2020 ; Huang et al, 2020 ). Extensive studies have shown that the intestine microbiota of aquatic animals is strongly affected by diet composition, trophic level, and developmental stage ( Rungrassamee et al, 2013 ; Yan et al, 2016 ; Xiong et al, 2017 ; Liu et al, 2018 ; Walburn et al, 2019 ). These studies have primarily focused on assessing how the intestine microbiota of aquatic animals is affected by biotic factors but ignored abiotic factors.…”
Section: Introductionmentioning
confidence: 99%
“…These may act on the gastrointestinal tract (GIT) directly to maintain the balance of the microorganism and promote development of the GIT. For example, YC can signi cantly affect community structure and composition of gut microbiota of grass carp, increasing the abundance of bene cial bacteria [11] . Addition of YC in the diet resulted in an increase in bene cial bacteria, making greater compensatory weight gains in weanling pigs [12] .…”
Section: Introductionmentioning
confidence: 99%